The multidiverse graphene oxide: How the fine structure affects structural analysis and performance in reverse osmosis membranes - Christian E. Halbig; Rahul Zambare; Bristy Mukherjee; Slaven Garaj (Carbon Trends)
For a comparative study, we obtained 27 different commercially available graphene oxide samples (GOs) from around the world and applied a wide range of destructive and non-destructive analytical techniques commonly used for structural analysis of graphene-based materials. Surprisingly, we found that a correlation of the recorded data did not follow significantly strong trends. This suggests that the fine structure and stereochemistry of individual GO samples, together with other macroscopic material parameters, are mainly responsible for the lack of comparability of the data obtained. Ultimately, these factors have a huge impact on the thermal degradation processes and also on the performance of GO in its subsequent application, as exemplified here for ion-water separation by reverse osmosis using GO-based membranes. This shows once again that graphene oxide is not the name of a single and well-defined nanomaterial, but rather the general term for a class of heterogeneous graphene-based materials with abundant oxo-functional groups and a wide range of physicochemical properties. The results presented should help researchers around the world to be aware of the vast differences behind the term GO and its associated properties.